Ecological implications of gene regulation by TfoX and TfoY among diverse Vibrio species. (12th March 2019) - Metzger, Lisa C.; Matthey, Noémie; Stoudmann, Candice; Collas, Esther J.; Blokesch, Melanie
Summary: Bacteria of the genus Vibrio are common members of aquatic environments where they compete with other prokaryotes and defend themselves against grazing predators. A macromolecular protein complex called the type VI secretion system (T6SS) is used for both purposes. Previous research showed that the sole T6SS of the human pathogen V. cholerae is induced by extracellular (chitin) or intracellular (low c‐di‐GMP levels) cues and that these cues lead to distinctive signalling pathways for which the proteins TfoX and TfoY serve as master regulators. In this study, we tested whether the TfoX‐ and TfoY‐mediated regulation of T6SS, concomitantly with natural competence or motility, was conserved in non‐cholera Vibrio species, and if so, how these regulators affected the production of individual T6SSs in double‐armed vibrios. We show that, alongside representative competence genes, TfoX regulates at least one T6SS in all tested Vibrio species. TfoY, on the other hand, fostered motility in all vibrios but had a more versatile T6SS response in that it did not foster T6SS‐mediated killing in all tested vibrios. Collectively, our data provide evidence that the TfoX‐ and TfoY‐mediated signalling pathways are mostly conserved in diverse Vibrio species and important for signal‐specific T6SS induction.